Determination of Heterocyclic Amines in Meat Matrices Using Enhanced Matrix Removal‐Lipid Extraction and Liquid Chromatography–Tandem Mass Spectrometry. Issue 7 (2nd July 2019) - Linghu, Ziyi; Karim, Faris; Taghvaei, Mostafa; Smith, J. Scott
Abstract: A simple, fast, and efficient method, "enhanced matrix removal of lipids" (EMR‐lipid), was proposed, optimized, and validated for identifying five polar heterocyclic amines (HCAs) in meat samples that ranged from high‐protein (beef and chicken) to high‐fat (pork bacon) matrices. The protocol involves an initial solid–liquid phase extraction followed by a rapid dispersive solid‐phase extraction using EMR‐lipid sorbents and salting‐out partitioning. Acetonitrile containing formic acid at two levels (1% and 2%) efficiently extracted HCAs from different meat matrices. Liquid chromatography–tandem mass spectrometry (MS/MS) with selective reaction monitoring mode was developed for qualitative and quantitative analysis. The highest MS/MS responses and better peak separation of analytes were achieved by adjusting mobile phases to pH 3.0 with instrumental detection limits between 0.01 and 0.05 ng/mL. Good linearity of standard curves was obtained in both pure solvents and postspiked meat extracts between 0.5 and 50.0 ng/mL. The validation results showed good precision, accuracy, and sensitivity for detecting HCAs in spiked meat samples. Satisfactory recoveries of four HCAs were achieved: 65% to 111% in beef, 71% to 106% in bacon, and 42% to 77% in chicken. Matrix effects were also assessed and showed less than –20% of ion suppression in bacon extract, while a medium to high signal suppression was observed in beef (–37% to –55%) and chicken (–28% to –52%). This optimized EMR‐lipid method provides acceptable results and advantages for determining trace level HCAs in complex meat matrices.